A Rotational Gyroscope with a Water-Film Bearing Based on Magnetic Self-Restoring Effect - Chen, Dianzhong; Liu, Xiaowei; Zhang, Haifeng; Li, Hai; Weng, Rui; Li, Ling; Rong, Wanting; Zhang, Zhongzhao (Sensors (Basel, Switzerland), 2018)
Stable rotor levitation is a challenge for rotational gyroscopes (magnetically suspended gyroscopes (MSG) and electrostatically suspended gyroscopes (ESG)) with a ring- or disk-shaped rotor, which restricts further improvement of gyroscope performance. In addition, complicated pick-up circuits and feedback control electronics propose high requirement on fabrication technology. In the proposed gyroscope, a ball-disk shaped rotor is supported by a water-film bearing, formed by centrifugal force to deionized water at the cavity of the lower supporting pillar. Water-film bearing provides stable mechanical support, without the need for complicated electronics and control system for rotor suspension. To decrease sliding friction between the rotor ball and the water-film bearing, a supherhydrophobic surface (SHS) with nano-structures is fabricated on the rotor ball, resulting in a rated spinning speed increase of 12.4% (under the same driving current). Rotor is actuated by the driving scheme of brushless direct current motor (BLDCM). Interaction between the magnetized rotor and the magnetic-conducted stator produces a sinusoidal rotor restoring torque, amplitude of which is proportional to the rotor deflection angle inherently. Utilization of this magnetic restoring effect avoids adding of a high amplitude voltage for electrostatic feedback, which may cause air breakdown. Two differential capacitance pairs are utilized to measure input angular speeds at perpendicular directions of the rotor plane. The bias stability of the fabricated gyroscope is as low as 0.5°/h.